The role of instructional leadership practices towards teacher's commitment - Chinna Thambi, Kasturi Telagam; Lope Pihie, Zaidatol Akmaliah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
This study was conducted to identify and explore the relationship among the role of instructional leadership practices and the commitment of the teachers in Malaysian primary school. This paper were developed based on four models. Instructional leadership model based on Hallinger Philip and Joseph Murphy Model, Joseph Murphy Model, Weber Model, and teacher’s commitment model were discussed in this paper. The purpose of this paper is to develop a conceptual model in exploring the relationship among transformational leadership, teachers’ empowerment and school effectiveness in Malaysia primary school. This conceptual paper were develop based on three theories; Transformational Leadership Theory, Empowerment Theory and School Effectiveness Theory. Based on extensive literature review, seven dimensions of transformational leadership (Avolio and Bass, 1992), six factors of teachers’ empowerment (Short and Rinehart, 1992) and eleven dimensions of school effectiveness (Mortimore, 1995) are identified to construct the model.